Blue Oceans Marketing Strategy: A Study of Refractory Industries inOdisha - Gochhait , Saikat; Tripathy , P. C. (Gyan Management Journal, 2014)
For refractory industries to be successful in terms of reasonable profit rate with multiplying sales and consistently rising market share, it is essential for these industries to adapt the most appropriate marketing strategy for creating new customers and their retention. Customer creation and customer retention are the two main strategies objectives of the marketing strategies of a modern business firm. Keeping in view the fast changing economic and non-economic environment and the volatile customer's expectations, new and sometimes unusual strategies are adopted by the marketers to enhance the sales. In this paper deals with the limitations of Red Ocean Marketing Strategy that promotes guerrilla marketing and brand wars and this has led to a fresh debate on ethical and legal grounds. Blue Ocean strategy that helps in creating uncontested market spaces has also been discussed highlighting its methodology principles that apply all types of refractory industries. In Blue Oceans, demand is created rather than fought over.
Keywords: Blue Ocean Strategy; Red Ocean Strategy; Globalized Environment; Refractory